2017
DOI: 10.5812/archneurosci.13250
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Protective Effects of Exercise on Cognitive Impairments Induced by Sleep Deprivation in Female Rats

Abstract: Sleep is an important factor in memory consolidation and brain health. In addition, sleep disorder is a common complaint among females in comparison with males. In menopausal females, to relieve sleep disturbances and other menopausal symptoms, hormone therapy may be used. Furthermore, although estrogen had helpful effects on the brain performance, hormone replacement therapy augmented unfavorable cardiovascular and oncological side effects. It is implied that exercise is a powerful nonpharmacological interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Previous studies have established the main important association between REM sleep and cognitive performances (Blechner, 2021; Diekelmann & Born, 2010; McCoy & Strecker, 2011). Paradoxical SD induces disorders in various types of cognitive functions such as learning and memory (Saadati, 2017; Taheri & Irandoust, 2020; Zagaar et al, 2013). The animals that experienced SD confirmed significant learning and memory diminishing in different tasks such as radial arm water maze (Zagaar et al, 2013), MWM (Saadati et al, 2015), and as well plus‐maze discriminative avoidance tasks (Alvarenga et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have established the main important association between REM sleep and cognitive performances (Blechner, 2021; Diekelmann & Born, 2010; McCoy & Strecker, 2011). Paradoxical SD induces disorders in various types of cognitive functions such as learning and memory (Saadati, 2017; Taheri & Irandoust, 2020; Zagaar et al, 2013). The animals that experienced SD confirmed significant learning and memory diminishing in different tasks such as radial arm water maze (Zagaar et al, 2013), MWM (Saadati et al, 2015), and as well plus‐maze discriminative avoidance tasks (Alvarenga et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the neuroprotective and helpful impacts of exercise and EE on cognition are mediated via BDNF and its receptors, tyrosine kinase (TrKB) (Dandi et al, 2018;Novkovic et al, 2015). Other evidence indicated that the increase in BDNF level by exercise is an important mechanism to protect against SD-induced cognitive impairments (Saadati, 2017;Saadati, Sheibani, Esmaeili-Mahani, Darvishzadeh-Mahani, et al, 2014;Zagaar et al, 2013). Our findings are supported by those of other works demonstrating that enriched condition has a dominant influence on neurotrophic gene expression and protein levels in several parts of the brain, mostly in the hippocampus (M. J.…”
Section: Discussionmentioning
confidence: 99%